Epidemiologi Kejadian Demam Berdarah Dengue di Kota Ternate, Maluku Utara - Tomia, Sumiati; Hadi, Upik Kesumawati; Soviana, Susi; Retnani, Elok Budi (Jurnal Veteriner, 2020)
Dengue Hemorrhagic Fever (DHF) is an endemic disease and it’s still a health problem in Ternate City. DHF is reported to occur every year and spread throughout the Districts in the Ternate Island region. Studies with epidemiological approaches according to people, places, and times that describe the incidence of DHF within a period of 10 years need to be known as an evaluation in the control program. The variables examined in this study were gender, age, number of deaths, the incidence of DHF in the subdistrict, and endemicity status. The results showed that male families suffered more DHF than female with 507 male sufferers while 411 female sufferers. The majority of DHF in the age group of 5-14 years with 507 people. The number of deaths resulting from dengue fever cases in 10 years was 31 people. The highest DHF incidence rate was in South Ternate sub-district with 379 cases and the lowest was in Ternate Island sub-district with 15 cases. Endemicity status in 2019 is endemic nine villages, sporadic 45 and seven potential villages. The conclusion of this study is the incidence of dengue hemorrhagic fever is more in men, with the age group of 5-14 years. DHF occurs throughout the year in all districts within the Ternate City area.